High-sensitivity troponin I with or without ultra-sensitive copeptin for the instant rule-out of acute myocardial infarction - Ricci, Fabrizio; Neumann, Johannes T.; Rübsamen, Nicole; Sörensen, Nils A.; Ojeda, Francisco; Cataldo, Ivana; Zeller, Tanja; Schäfer, Sarina; Hartikainen, Tau S.; Golato, Maria; Palermi, Stefano; Zimarino, Marco; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background:The instant, single-sampling rule-out of acute myocardial infarction (AMI) is still an unmet clinical need. We aimed at testing and comparing diagnostic performance and prognostic value of two different single-sampling biomarker strategies for the instant rule-out of AMI. Methods:From the Biomarkers in Acute Cardiac Care (BACC) cohort, we recruited consecutive patients with acute chest pain and suspected AMI presenting to the Emergency Department of the University Medical Center Hamburg-Eppendorf, Hamburg, Germany. We compared safety, effectiveness and 12-month incidence of the composite endpoint of all-cause death and myocardial infarction between (i) a single-sampling, dual-marker pathway combining high-sensitivity cardiac troponin I (hs-cTnI) and ultra-sensitive copeptin (us-Cop) at presentation (hs-cTnI ≤27 ng/L, us-Cop <10 pmol/L and low-risk ECG) and (ii) a single-sampling pathway based on one-off hs-cTnI determination at presentation (hs-cTnI <5 ng/L and low-risk ECG). As a comparator, we used the European Society of Cardiology (ESC) 0/1-hour dual-sampling algorithm. Results:We enrolled 1136 patients (male gender 65%) with median age of 64 years (interquartile range, 51-75). Overall, 228 (20%) patients received a final diagnosis of AMI. The two single-sampling instant rule-out pathways yielded similar negative predictive value (NPV): 97.4% (95%CI: 95.4-98.7) and 98.7% (95%CI: 96.9-99.6) for dual-marker and single hs-cTnI algorithms, respectively (P=0.11). Both strategies were comparably safe as the ESC 0/1-hour dual-sampling algorithm and this was consistent across subgroups of early-comers, low-intermediate risk (GRACE-score <140) and renal dysfunction. Despite a numerically higher rate of false-negative results, the dual-marker strategy ruled-out a slightly but significantly higher percentage of patients compared with single hs-cTnI determination (37.4% versus 32.9%; P<0.001). There were no significant between-group differences in 12-month composite outcome. Conclusions:Instant rule-out pathways based on one-off determination of hs-cTnI alone or in combination with us-Cop are comparably safe as the ESC 0/1h algorithm for the instant rule-out of AMI, yielding similar prognostic information. Instant rule-out strategies are safe alternatives to the ESC 0h/1h algorithm and allow the rapid and effective triage of suspected AMI in patients with low-risk ECG. However, adding copeptin to hs-cTn does not improve the safety of instant rule-out compared with the single rule-out hs-cTn at very low cut-off concentrations.